Integrated Project Management: The Role of Communication, Risk, Quality, and Procurement in Project Success at PT Teknologi Gotong Royong - Firman, Nofirman Yantoni Waruwu; Kresnapati, Kresnapati Pribadi Kusdarwanto; Mala, Nurmala Sari; Hadi, Hadi Supratikta (Universitas Pamulang, 2026)
This study aims to analyze the role of integrated project communication management, risk management, quality management, and procurement management in enhancing project success at PT Teknologi Gotong Royong. The research employs a descriptive design with a quantitative approach, using purposive sampling of 25 respondents directly involved in property digitalization projects, complemented by interviews, observations, and documentation. Data were analyzed using multiple linear regression with the assistance of statistical software. The findings show that all variables—communication management, risk management, quality management, and procurement management-have a significant influence on project success, with a coefficient of determination (R²) of 0.791. Communication management has the strongest influence, followed by quality management, risk management, and procurement management. These results indicate that project success is strongly determined by the synergy among integrated project management aspects; therefore, the company must strengthen cross-division coordination, enhance risk mitigation, maintain consistent quality, and ensure effective procurement processes to support optimal project outcomes.